Cancer Risk of Peutz–Jeghers Syndrome and Treatment Experience: A Chinese Medical Center - Xu, Zuxin; Gu, Guoli (Clinics in Colon and Rectal Surgery, 2023)
Peutz–Jeghers syndrome (PJS), also known as hereditary mucocutaneous pigmented gastrointestinal polyposis, is a clinically rare autosomal dominant genetic disease, which falls into the category of hereditary colorectal cancer. There are ∼7,000 new cases of PJS in China every year, and 170,000 PJS patients may survive for a long time in society. PJS polyps are characterized by an early age of onset, difficult diagnosis and treatment, and easy recurrence. With repeated growth, polyps can lead to serious complications such as intestinal obstruction, intussusception, gastrointestinal bleeding, and cancerization, which cause serious clinical problems. Due to repeated hospitalization and endoscopic follow-up, PJS patients and their families suffer from great physical and mental pain and economic burden. With the in-depth understanding of PJS and the development and popularization of endoscopic techniques in the past decade, an integrated treatment modality based on endoscopy plus surgery has gradually become the preferred treatment in most hospitals, which greatly improves the quality of life of PJS patients. However, there is still a lack of effective drug prevention and cure means. In this paper, the current clinical treatment means for PJS polyps were summarized by literature review combined with the treatment experience of our medical center, with a focus on their clinical diagnosis, treatment, and cancer risk.
Keywords: Peutz–Jeghers syndrome; treatment; cancer risk; operation